2016
DOI: 10.2320/matertrans.m2016030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Kind of Metal Cation on Corrosion Mechanism of A3003 Aluminum Alloy in Tap Water

Abstract: Effect of a kind of metal cation on corrosion mechanism of A3003 aluminum alloy in tap water was investigated by electrochemical techniques and immersion corrosion tests. Corrosion rate of the aluminum alloy decreased with increase in a hardness of cation, except for Mg 2+ . XPS analyses showed metal cations, classi ed as a hard acid in tap water were incorporated in hydroxides on the aluminum alloy. The results suggest that the incorporated cations have corrosion inhibitory effect (e.g., Ca 2+ and Zn 2+ ) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Commonly, Zn 2+ is categorized as a hard acid and OH − as a hard base; from this, it may be proposed that Zn 2+ easily bonds with the OH − on the Al 2 O 3 layer on aluminum alloys (Figure A). Our previous study established that a metal cation layer of Zn 2+ (10‐ to 15‐nm thickness) was formed on Al 2 O 3 in model fresh water containing Zn 2+ and that the metal cation layer had high corrosion protective properties (Figure B) . In the previous study, the polarization curve for A3003 aluminum alloy obtained in model fresh water containing Zn 2+ suggested that the metal cation layer of Zn 2+ on the aluminum alloy suppresses both the anodic (metal oxidation) and cathodic (oxygen reduction) reactions.…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…Commonly, Zn 2+ is categorized as a hard acid and OH − as a hard base; from this, it may be proposed that Zn 2+ easily bonds with the OH − on the Al 2 O 3 layer on aluminum alloys (Figure A). Our previous study established that a metal cation layer of Zn 2+ (10‐ to 15‐nm thickness) was formed on Al 2 O 3 in model fresh water containing Zn 2+ and that the metal cation layer had high corrosion protective properties (Figure B) . In the previous study, the polarization curve for A3003 aluminum alloy obtained in model fresh water containing Zn 2+ suggested that the metal cation layer of Zn 2+ on the aluminum alloy suppresses both the anodic (metal oxidation) and cathodic (oxygen reduction) reactions.…”
Section: Resultsmentioning
confidence: 80%
“…The formation and corrosion protection mechanism of the metal cation layer of Zn 2+ is detailed in Figure A and B. Several studies have reported that an Al 2 O 3 layer (5‐ to 10‐nm thickness) is formed on aluminum alloys and that the layer has OH − sites at the solution/Al 2 O 3 interface . Hard and soft acids and bases (HSAB) theory has reported that hard acids and hard bases form strong bonds .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations